(untitled) (2014)
During the requirements elicitation process, a group of analysts and stakeholders identify, capture, and integrate requirements. Textual or graphic descriptions capturing the most relevant concepts from the domain of a software application development are generated. Commonly, the initial phases-identifying and capturing requirements expressed in natural language-are executed by using techniques in which high analyst intervention and comprehensive knowledge of the context and the problem domain are required. Thus, a subjective, ambiguous, and error-prone process is implied, causing losses in the generation of the initial domain models (specified in a controlled language). In this paper we provide a synthesis of trends and conceptual approaches found in the state of the art concerning the natural language transformation into controlled language during the requirements elicitation process. Finally, we propose a pre-conceptual schema for representing the conceptual framework of the transformation process.